Analisis Dampak Krisis Ekonomi Terhadap Tingkat Ekonomi Makro Di Wilayah Bali - Rezzylina Dwi Akhirulyati; Andrew Ari Fardana; Muhammad Yasin (Universitas 45 Surabaya, 2023)
This study aims to determine the impact of the economic crisis caused by the spread of the Covid 19 virus on the macroeconomic level in Bali. This research method uses qualitative methods and library research. Data collection techniques, namely recording important information in conducting data analysis by means of data reduction, displaying data and drawing conclusions so as to get conclusions. The results of the study show that the impact of the economic crisis caused by the spread of Covid 19 is very significant for the macroeconomic level of the Bali region. Bali is an area that is well-known for tourism so that most of Bali's Regional Original Revenue is based on the tourism sector. The lack of visitors coming from both local and foreign countries has caused Bali's original regional income to decrease and this has affected the country's foreign exchange earnings. The government's role in maintaining the welfare of its people who are fawning over Covid 19 has also caused the government's debt to increase to purchase social assistance to the community. Companies that are involved in the world of tourism are advised to maintain their health while adhering to health protocols to avoid another Covid-19 virus attack. The Bali government is also expected to be able to provide services to companies and communities affected by Covid 19 in providing jobs.